MATHEMATICS TEACHERS’ PROFESSIONAL DEVELOPMENT: A BIBLIOMETRIC ANALYSIS - Nur Choiro Siregar; Siti Nasiah (Universitas Tadulako, 2022)
Mathematics is one of the essential subjects for developing a national economy. It is the fourth element of the STEM acronym. Therefore, teachers’ abilities need to be enhanced for the learning process to be effective. However, the majority of mathematics teachers in developing countries still have difficulty in obtaining professional development. The present study aims to identify the targets of mathematics teachers’ professional development (MTPD) and examines its prominence in the literature over the past five years. It takes the form of a systematic review. The first objective is realized through the use of a qualitative, deductive, and thematic approach. The second objective is realized using the VOSviewer software tool (version 1.6.15.0). The 28 articles identified in the study were sourced from the Scopus database and published between 2016 and 2020. The results show that MTPD focuses on the implementation of technology, inquiry-based learning, problem-solving, and contextual (real-world) problems in the teaching and learning (T&L) process. The term was most often related to “mathematics,” “professional development,” “study,” and “teacher.” The results of the network visualization analysis of MTPD incorporate (a) professional development-teacher; (b) professional development-mathematics; (c) professional development-learning; and (d) professional development-mathematics teacher. The results of the study have implications for teachers trying to implement a T&L strategy that actively involves students in solving mathematical problems. It is recommended that future researchers identify MTPD in reference to (a) age; (b) gender; (c) the duration of teaching, (d) teaching location (urban and rural), and (e) the need to use more databases.